2016
DOI: 10.1136/bmjopen-2016-012113
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of sleep in suicide risk: qualitative interview study

Abstract: ObjectiveSleep problems are associated with increased risk of suicide, independent of depression. This analysis explores narrative accounts of the role of sleep in relation to suicidal thoughts and behaviours.DesignQualitative study, based on in-depth semistructured interviews which were analysed with an inductive, latent thematic analysis.ParticipantsA maximum variation sample of 18 people with experience of a major depressive episode, and suicidal thoughts and behaviours.SettingPrimary care, North West Engla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 45 publications
4
65
0
1
Order By: Relevance
“…These psychological effects are corroborated in a qualitative study recently conducted by Littlewood et al [50]. In their study, suicide attempters identified sleep duration as one of the factors influencing the development of suicidal behaviours.…”
Section: Short Sleep Duration and Suicidal Behavioursupporting
confidence: 59%
See 2 more Smart Citations
“…These psychological effects are corroborated in a qualitative study recently conducted by Littlewood et al [50]. In their study, suicide attempters identified sleep duration as one of the factors influencing the development of suicidal behaviours.…”
Section: Short Sleep Duration and Suicidal Behavioursupporting
confidence: 59%
“…Additionally, in the qualitative study conducted by Littlewood et al [50], suicide attempters refer that being awake during the biological night made them more prone to focus on negative thoughts (fewer distractions from the outside world), leading to introspectiveness, rumination, and negative self-appraisal.…”
Section: Sleep Circadian Rhythms and Suicidal Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence about the relationship between sleep and suicidal behaviour, but some authors state that this relationship needs further investigation. A study involving people with suicidal thoughts or with a history of attempted suicide revealed that at night, when everything is quiet, it is difficult to keep from having negative thoughts (Littlewood et al 2016). Another study found that problems with falling asleep and excessive sleeping may be associated with an increased risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Sleeping well means that people can manage everyday life, but if sufficient sleep is not achieved, life can become more difficult (Littlewood et al 2016). One study concluded that suicide attempts could be reduced by treating sleep disorders.…”
Section: Discussionmentioning
confidence: 99%